Improving Student Learning Outcomes During The Covid-19 Pandemic Using Learning Videos and E-Learning - A. Jauhar Fuad; Pranita Andhinasari (Institut Agama Islam Tribakti Kediri, 2021)
The problem that arises in learning in the Covid-19 era is unilateral learning centered on teacher activities, by giving assignments. Students only work on assignments and then the work is photographed and sent via whatsapp, causing students to lack understanding of the material and reluctant to do assignments. The solution to the problems above is the use of video for learning and e-learning. This research phase begins with action planning, action implementation, observation and reflection. This stage is repeated until the expected increase in learning outcomes is achieved, and does not require further improvement. The final result analysis showed that in the pre-learning cycle the percentage of classical completeness was 27.28%. In the first cycle there was an increase in classical completeness reaching 54.5%. In the second cycle there was an increase in classical completeness reaching 91%. Thus, it can be concluded that the use of video for learning and e-learning during the covid-19 pandemic is able to improve student learning outcomes. [Permasalahan yang muncul dalam pembelajaran di era Covid-19 adalah pembelajaran sepihak yang dipusatkan pada kegiatan guru. Dengan pemberian tugas siswa hanya mengerjakan tugas kemudian karya tersebut difoto dan dikirim melalui whatsapp sehingga menyebabkan siswa kurang memahami materi dan enggan mengerjakan tugas. Solusi dari permasalahan di atas adalah pemanfaatan video untuk pembelajaran dan e-learning. Tahap penelitian ini dimulai dengan perencanaan tindakan, pelaksanaan tindakan, observasi dan refleksi. Tahap ini diulangi sampai tercapai peningkatan hasil belajar yang diharapkan, dan tidak memerlukan perbaikan lebih lanjut. Analisis hasil akhir menunjukkan bahwa pada siklus pra pembelajaran persentase ketuntasan klasikal sebesar 27,28%. Pada siklus I terjadi peningkatan ketuntasan klasikal mencapai 54,5%. Pada siklus II terjadi peningkatan ketuntasan klasikal mencapai 91%. Dengan demikian, dapat disimpulkan bahwa pemanfaatan video untuk pembelajaran dan e-learning di masa pandemi covid-19 mampu meningkatkan hasil belajar siswa]